Upaya Optimalisasi Lahan Pekarangan melalui Pelatihan Teknik Budidaya Cabai Rawit Terpadu dan Inisiasi Pembentukan KWT pada Kelompok Hidayah Tani di Jember, Jawa Timur - Indri Fariroh; Nurul Dwi Novikarumsari; Ratih Apri Utami (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Hidayah Tani Farmers Group is a farmer's institution in Jember, East Java. The potential for large cayenne pepper productivity is around 523 tons, but most members of the Farmers Group still prioritize farming with rice-rice-palawija and rice-rice-tobacco cropping patterns. Meanwhile, cayenne pepper as a local potential has not become a priority because of the lack of technical knowledge about cayenne pepper cultivation. This group has several needs in terms of assistance and economic empowerment through farmer group institutions. Through group-based institutions, farmers can get counseling and assistance related to the cultivation of cayenne pepper in an integrated manner by utilizing their yards. Service activities are carried out through socialization of service programs, providing integrated cayenne pepper cultivation assistance, conducting counseling related to institutional strengthening of farmer groups, and monitoring and evaluation. Farmers' responses to the implementation of the mentoring program showed that the participants' perception of the cayenne pepper cultivation technique was good, and the women agreed that there would be a Women Farmers Group formed.